PENGARUH HARGA, LOKASI DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN PADA USAHA AYAM GEPREK BERKAH SUMBAWA - Sabirah, Humayrah Iffah; Mandasari , Jayanti (Jurnal Nusa Manajemen, 2025)
This study aims to testing the effect of Price, Location and Word of Mouth on Purchasing Decisions at the Sumbawa Blessing Geprek Chicken business. This study uses an associative quantitative approach with 100 samples who are consumers of Ayam Geprek Berkah selected through purposive sampling technique then the sample is determined using the Pauleedy formula.. This research instrument is a questionnaire consisting of four variables, namely price, location, word of mouth and purchasing decisions which have been tested for validity and reliability. Data analysis using multiple linear regression with the results showed that the t value of the price variable table (3.470> 1.984) with a significance value (Sig.) of 0.001 <0.05, which means that the price variable has an effect on purchasing decisions. Then the results of the t table value of the location variable (1.483 < 1.984) with a significance value (Sig.) 0.141> 0.05, which means that the location variable has no effect on purchasing decisions. The results of the t table value of the word of mouth variable (2.805> 1.984) with a significance value (Sig.) of 0.006 <0.05 indicate that the word of mouth variable has an effect on purchasing decisions.